GE_GERICHTE P/6276/2018 vom 26. Juni 2019 - GE Cour de justice (2019)
INCENDIE PAR NÉGLIGENCE;RESPONSABILITÉ DE L'ENTREPRISE;LIEN DE CAUSALITÉ;CLASSEMENT DE LA PROCÉDURE | CPP.319.al1.leta; CP.222.al1; CP.11; CP.12.al3; CP.102.al1